Using various artificial soil mixtures to restore dry grasslands in quarries. Issue 7 (17th February 2022) - Chenot‐Lescure, Julie; Jaunatre, Renaud; Buisson, Elise; Ramone, Hervé; Dutoit, Thierry
Abstract : Quarry restoration is difficult to implement due to the scarcity of the original soil. The restoration of Mediterranean dry grasslands to mitigate similar ecosystem/habitat loss is thus still a developing process. So far, very few studies have created artificial substrates to address the lack of soil. In the La Crau plain (Southeastern France), quarries were established in an ancient Mediterranean steppe‐like dry grassland. Once the remaining grassland zones were protected in 2001, quarries were extended over former intensive orchards established on the grassland in the 1990s before it was protected. Now, restoration has to be done without the unaltered protected grassland soil but with the soil from orchards, which contains fertilizers spread during the orchard exploitation. To recreate a more suitable substrate, the orchard topsoil was mixed with poor substrate materials directly extracted from the quarry (0–30 mm pebbles with sandy matrix). Different substrate mixtures were tested with or without sowing the dominant species of the grassland, a perennial grass: Brachypodium retusum (and an annual grass B. hybridum ). After 5 years of monitoring, our results show that raw substrate materials (100%) limit the establishment of all species, and that, at the opposite, orchard topsoil (100%) favors a significantly higher species richness of target and non‐target species. The recommended substrate mixture to reach a compromise between high target species cover and low non‐target species cover is composed of 50% raw quarry material and 50% arable soil. Sowing Brachypodium not only limits non‐target species richness and cover but also reduces target species richness establishment.